PENGEMBANGAN TIMBANGAN BUAH ANALOG MENJADI DIGITAL BERBASIS MIKROKONTROLER ATMEGA16 - , ELOK HARDIYATI RUSNINDYO, Muhammad Arrofiq, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A scale is used for measuring the load. The digital scale is developed to help the user in reading the measurement and to avoid a mistaken measurement. In this research, the measurement of load used a sensor, which is known as Load Cell. As the result, the output voltage is then converted into digital data by ADS7822. The resulted digital data is further processed by microcontroller ATmega16, hence the data can be visibly displayed in the LCD screen along with its gram unit. Based on the measurement of determined loads using the developed digital scale, showed that the results was consistent with the weight of determined samples.